Neoliberalisation enacted through development aid: the case of health vouchers in India. Issue 2 (15th March 2022) - Hunter, Benjamin M.; Bisht, Ramila; Murray, Susan F.
ABSTRACT: Despite a history of critical scholarship on development aid and neoliberalism in public health, very little specific attention has been drawn to how a tripling in aid commitments in the health sector after the Millennium Declaration created new opportunities for the advancement of neoliberal ideas and practices. Here we examine an externally funded aid project in Uttar Pradesh, India that seemed to embrace important public health and access to care concerns but that can also be understood as part of a larger – and damaging – ideological project. We adopt a contextualising and process-oriented understanding of 'neoliberalisation' to examine its design and enactment. We also show how these policies were unevenly resisted and advanced by the politicians and civil servants who were expected to guide them through different levels of government on the way to implementation. On the frontline, programme workers and users tactically re-interpreted the notion of 'choice' to serve their interests in ways that were not anticipated by programme designers. In the case of the programme workers, these reflected the individualised performance targets set up by the programme and an existing culture of clientelism. Our analysis challenges uncritical portrayals of development assistance for health as a beneficent reallocation of resources.